Evaluation on Health Policy Implementation for Decreasing Maternal Mortality Rate through Prenatal Class Program in East Ogan Komering Ulu, South Sumatera - Saragih, Elfina; Purwadi, Hari; Isharyanto, Isharyanto (Journal of Health Policy and Management, 2019)
Background: An indicator to determine public health is maternal mortality rate (MMR). Based on the Indonesian Demographic and Health Survey (IDHS) in 2012, MMR in Indonesia was still at 359 per 100,000 live births. Community participation is very supportive in efforts to reduce maternal mortality through prenatal class. This study aimed to explore the implementation of prenatal class as an effort to reduce maternal mortality.Subjects and Method: This was a qualitative descriptive study. The study was carried out in east Ogan Komering Ulu, South Sumatera, Indonesia. Key informants consisted of 5 subjects namely Head of east Ogan Komering Ulu Health Office, Head of family health section, Head of Rawa Bening Health Center, 10 midwives, and head village. The data were collected by in-depth interview, observation, and document review.Results: Prenatal class activities in Rawa Bening community health center have been implemented for a long time. Stakeholders worked together in accordance with their respective tasks and functions. Prenatal class activities have resulted in increased knowledge of mothers and families about pregnancy, postpartum care, newborn care, and family planning. However, pregnant women who were participated in prenatal class was still low.Conclusions: Prenatal class program in east Ogan Komering Ulu, has been implemented according to the implementation guidelines. However, pregnant women who were participated in prenatal class is still low.Keywords: maternal class program, maternal mortality rate, evaluationCorrespondence: Elfina Saragih. Masters Porgram in Law, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: elfinasaragih@gmail.com. Mobile: +628527066626 Journal of Health Policy and Management (2019), 4(2): 111-116https://doi.org/10.26911/thejhpm.2019.04.02.06